مصحف،صحف اور قرآن کے باہمی فروق اور اصطلاحی مفاہیم کا تحقیقی مطالعہ: A Research Study of the Mutual Differences and Terminological Meanings of the Muṣḥaf, Ṣuḥuf, and the Qurʾān (Contemporary Journal of Social Science Review, 2025)
This article explains the difference between the terms Qurʾān, Ṣuḥuf, and Muṣḥaf by studying their meanings, historical use, and scholarly explanations. During the lifetime of the Prophet Muhammad ﷺ, the Qurʾān was not collected in the form of a single bound book. Instead, it was memorized and written on separate materials such as parchment, bones, stones, and leaves. These written pieces are referred to as ṣuḥuf. After the Prophet’s death, the Qurʾān was first gathered in written form during the caliphate of Abū Bakr (RA) and later standardized and compiled into a single, complete book during the caliphate of ʿUthmān b. ʿAffān (RA). It was at this stage that the term muṣḥaf became commonly used. Classical scholars explain that ṣuḥuf refers to separate, unbound pages, while muṣḥaf means a complete written copy of the Qurʾān bound between two covers. The article also clarifies that the word muṣḥaf was not used as a formal name for the Qurʾān during the Prophetic period. Rather, it describes the physical written form of the Qurʾān, not the divine revelation itself. Differences found in some personal copies prepared by individual Companions do not represent differences in the Qurʾān, since the entire Muslim community agreed upon the Muṣḥaf ʿUthmānī. Finally, the article responds to certain Orientalist claims that confuse variations in written copies (muṣḥaf) with variation in the Qurʾānic text. It shows that such misunderstandings arise from failing to distinguish between the Qurʾān as God’s revealed speech and the muṣḥaf as its written record.